A tool for protected area management: multivariate control charts 'cope' with rare variable communities. Issue 6 (1st May 2013) - Stringell, Thomas B.; Bamber, Roger N.; Burton, Mark; Lindenbaum, Charles; Skates, Lucie R.; Sanderson, William G.
Abstract Performance assessment, impact detection, and the assessment of regulatory compliance are common scientific problems for the management of protected areas. Some habitats in protected areas, however, are rare and/or variable and are not often selected for study by ecologists because they preclude comparison with controls and high community variability makes meaningful change detection difficult. Shallow coastal saline lagoons are habitats that experience comparatively high levels of stress due to high physical variability. Lagoons are rare, declining habitats found in coastal regions throughout Europe (and elsewhere) where they are identified as one of the habitats most in need of protected area management. The infauna in the sediments of 25 lagoons were sampled. Temporal and spatial variation in three of these [protected] lagoons was investigated further over 5 years. In a multivariate analysis of community structure similarities were found between some lagoons, but in other cases communities were unique or specific to only two sites. The protected lagoons with these unique/specific communities showed significant temporal and spatial variation, yet none of the changes observed were attributed to human impacts and were interpreted as inherent variability. Multivariate control charts can operate without experimental controls and were used to assess community changes within the context of 'normal' lagoon variability. The aim of control chart analysis is to characterize background variability in a parameter and identify when a new observation deviates more than expected. In only 1 year was variability more than expected and corresponded with the coldest December in over 100 years. Multivariate control charts are likely to have wide application in the management of protected areas and other natural systems where variability and/or rarity preclude conventional analytical and experimental approaches but where assessments of condition, impact or regulatory compliance are nonetheless required.